2018
DOI: 10.2478/psicolj-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic and skin temperature indices of vigilance and inhibitory control

Abstract: Neurophysiological markers of the ability to sustain attention and exert inhibitory control of inappropriate responses have usually relied on neuroimaging methods, which are not easily applicable to real-world settings. The current research tested the ability of electroencephalographic and skin temperature markers to predict performance during the Sustained Attention to Response Task (SART), which demands vigilance and inhibitory control. In Experiment 1, we recorded the electroencephalogram (EEG) during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Moreover, while in Lara et al (2018) P3 decreased across time-on-task, in Bonnefond et al (2010) late P1 rather increased across blocks. Late ERPs (i.e., as P3 or late P1) changes across time-on-task have received diverse interpretations by resources theories: while a decrease in amplitude has been proposed as a marker of resource depletion with time-on-task (Lara et al, 2018;Warm et al, 2008), increased amplitude has been associated with increased effort to keep resources allocation on the external task (Bonnefond et al, 2010;Koelega et al, 1992).…”
Section: F I G U R Ementioning
confidence: 80%
See 2 more Smart Citations
“…Moreover, while in Lara et al (2018) P3 decreased across time-on-task, in Bonnefond et al (2010) late P1 rather increased across blocks. Late ERPs (i.e., as P3 or late P1) changes across time-on-task have received diverse interpretations by resources theories: while a decrease in amplitude has been proposed as a marker of resource depletion with time-on-task (Lara et al, 2018;Warm et al, 2008), increased amplitude has been associated with increased effort to keep resources allocation on the external task (Bonnefond et al, 2010;Koelega et al, 1992).…”
Section: F I G U R Ementioning
confidence: 80%
“…Previous evidence is both scarce and inconsistent regarding ERPs associated with the executive vigilance decrement, as either increased (Lara et al, 2018), decreased (Boksem et al, 2005), or similar (Reteig et al, 2019) N1 across time‐on‐task has been reported. Moreover, while in Lara et al (2018) P3 decreased across time‐on‐task, in Bonnefond et al (2010) late P1 rather increased across blocks. Late ERPs (i.e., as P3 or late P1) changes across time‐on‐task have received diverse interpretations by resources theories: while a decrease in amplitude has been proposed as a marker of resource depletion with time‐on‐task (Lara et al, 2018; Warm et al, 2008), increased amplitude has been associated with increased effort to keep resources allocation on the external task (Bonnefond et al, 2010; Koelega et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Skin temperature (ST) is a rather simple experimental methodology in which a sensor records the temperature of the participant. Even though the use of skin temperature in psychological research date back many years (see Maslach et al, 1972) and has attracted attention in cognitive science research due to its cost-effectiveness and simplicity of use (Lara et al, 2018), this method has not found as many applications as the other methodologies listed above.…”
Section: Use Of Physiological Measuresmentioning
confidence: 99%
“…These features therefore make the recording of skin temperature a valid method in Neuroergonomics research. Research has revealed that increments in the DPG were associated with earlier sleep latency and higher somnolence at the beginning of the night (Kräuchi et al, 1999), and with lower task performance in vigilance tasks like the SART (Lara et al, 2018) and the PVT (Romeijn and Van Someren, 2011; Molina et al, 2017). Altogether, these findings suggest that skin temperature (mainly the DPG) could be used as a neuroergonomic marker of vigilance.…”
Section: Introductionmentioning
confidence: 99%